2003
DOI: 10.1016/s0040-6090(03)01048-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and butanol/ethanol sensing properties of mixed tungsten oxide and copper tungstate films obtained by spray–sol–gel

Abstract: Mixed WO 3 -CuWO 4 films have been prepared from aqueous solution of copper sulfate and polytungsten gel with molar ratio Cu/W from 0 to 100 %. These solutions were sprayed onto alumina substrates at 220 ºC. The obtained films were amorphous, and crystallized after an annealing at 300 ºC in air for 3 h. The annealed films were composed by a mixture of CuWO 4 and WO 3 phases. The film obtained from a solution with an equimolar ratio of Cu/W was a pure CuWO 4 . The pure WO 3 films obtained have a high surface "i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Several physical or chemical synthesis routes, i.e., deposition by spray [18], deposition via pulsed laser [19], radio-frequency assisted sputtering deposition [20], sol-gel method [21], fabrication in solidphase [22], surfactant aided precipitation [23] and fabrication in polyol-media [24] have been utilized for the preparation of different morphologies of copper tungstate nanoparticles, i.e., nanofilm, nanosphere, and porous film. These methods have own advantages; however, each of them suffers from some restrictions such as requiring for the strictly controlled synthesis media, high synthesis costs, and complexities in the synthesis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Several physical or chemical synthesis routes, i.e., deposition by spray [18], deposition via pulsed laser [19], radio-frequency assisted sputtering deposition [20], sol-gel method [21], fabrication in solidphase [22], surfactant aided precipitation [23] and fabrication in polyol-media [24] have been utilized for the preparation of different morphologies of copper tungstate nanoparticles, i.e., nanofilm, nanosphere, and porous film. These methods have own advantages; however, each of them suffers from some restrictions such as requiring for the strictly controlled synthesis media, high synthesis costs, and complexities in the synthesis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Table 1 Lattice parameters of copper tungstate, CuWO4, as determined by different authors (triclinic structure, space group P1). different routes are applied for obtaining high-quality CuWO 4 in the form of bulk crystals (e.g., slow-cooled indirect flux reaction technique [17,18], recrystallization in an ampoule for chemical vapour transport [19]), films on different substrates (e.g., spray-sol-gel deposition [20], radio-frequency (RF) sputtering deposition [21]) or nanocrystalline powders possessing poor agglomeration of crystallites [22]. When measuring electrical conduction of a single-crystal copper tungstate, Bharati et al [23] have shown that CuWO 4 is an intrinsic semiconductor with the band gap, E g , 1.52 eV.…”
Section: Introductionmentioning
confidence: 99%
“…SnO 2 sols were obtained from tin alkoxide Sn(t-OAm) 4 or tin salt (SnCl 4 .5H 2 O) precursors and stabilized with ammonia or tetrabutyl ammonium hydroxide (TEA-OH) as peptizers [21]. The sols prepared as described above were sprayed onto the substrates heated at 130 °C for 1 h. The gas carrier flux and air pressure were kept at 40 L/min and 1.5x10…”
Section: Methodsmentioning
confidence: 99%
“…After annealing at a temperature of 400 °C, the samples crystallized into SnO 2 with mean grain sizes of around 20 nm. The morphology of SnO 2 films obtained from SnCl 4 5H 2 O and (C 5 H 11 O) 4 Sn precursors and annealed at 500 °C for 2 h are shown in Figs. 12a and 12b, respectively.…”
Section: Films Obtained From Aqueous Solutionsmentioning
confidence: 99%
See 1 more Smart Citation